FODDER VALUES OF SHRUB SPECIES IN MAQUIS IN DIFFERENT ALTITUDES AND SLOPE ASPECTS - S. Temel; M. Tan (Journal of Animal and Plant Sciences, 2011)
The study was conducted to determine the nutritional value of the shrub species in the district of Erdemli-near the Taurus Mountains in Turkey during the period of April 2005 to April 2007. The samples were collected from three different altitudes (0-400 m, 400-800 m and over 800 m) and two geographical sides (north and south). In the study, CP (Crude Protein), NDF (Neutral Detergent Fibre) ve ADF (Acid Detergent Fibre) contents of the species were evaluated. The CP content in leaves of the shrub species ranged from 8.13% to 21.58%. NDF ratios were 27.38% to 52.62% and ADF ratios were 12.08% to 37.21%. The highest CP content (11, 98%) among altitudes was detected at 0-400 meters, and the highest NDF (43.98%) and ADF (30.07%) values were measured at 400-800 m elevation. Both CP (11.95%) and ADF (29, 95%) ratios in the northern slopes found to be higher than those in the southern slopes. However, we did not find statistically significant differences in NDF values of slope aspects.
Keywords: CP; NDF; ADF; shrub species; altitude; slope aspect